Форми і методи забезпечення антикорупційної політики України (на прикладі діяльності Державного комітету архівів України) - Овчар, І.В. (Архіви України, 2010)
У статті розкрито зміст роботи Державного комітету архівів України щодо запобігання і протидії корупції та застосування правових положень антикорупційного законодавства. В статье расскрыто содержание работы Государственного комитета архивов Украины относительно предотвращения и противодействия коррупции и применение правовых положений антикоррупционного законодательства. Legislative maintenance of an anticorruption politics of Ukraine studies and characterizes ways and methods of the prevention and counteraction of corruption offence. Studying of the given direction promotes information and analytical filling of a problem which concerns presence of corruption. The practical contents of maintenance of rules of law testify to introduction of a unique state anticorruption politics. This article we open the contents of the lead work concerning the prevention and counteractions of corruption of the State Committee on Archives of Ukraine.